SOME RESULTS OF ALTERNATING SYSTEMS - Gengrong Zhang, Jiankang Cheng, Xiaoting Li (International Journal of Research Science and Management, 2015)
In this paper , we talk about the relationship of f , g and g, f  . We show that : 1. f , g  g, f , f , g  g  f f  g ; 2. f , g  f , gg, f ..